NUMERICAL MODELLING OF STRAIN IN LAVA TUBES - Merle O. (My University, 2000)
The strain within lava tubes is described in terms of pipe flow. Strain is partitioned into three components: (a) two simple shear components acting from top to bottom and from side to side of a rectangular tube in transverse section; and (b) a pure shear component corresponding to vertical shortening in a deflating flow and horizontal compression in an inflating flow. The sense of shear of the two simple shear components is reversed on either side of a central zone of no shear. Results of numerical simulations of strain within lava tubes reveal a concentric pattern of flattening planes in section normal to the flow direction. The central node is a zone of low strain, which increases toward the lateral borders. Sections parallel to the flow show obliquity of the flattening plane to the flow axis, constituting an imbrication. The strain ellipsoid is generally of plane strain type, but can be of constriction or flattening type if thinning (i.e. deflating flow) or thickening (i.e. inflating flow) is superimposed on the simple shear regime. The strain pattern obtained from numerical simulation is then compared with several patterns recently described in natural lava flows. It is shown that the strain pattern revealed by AMS studies or crystal preferred orientations is remarkably similar to the numerical simulation. However, some departure from the model is found in AMS measurements. This may indicate inherited strain recorded during early stages of the flow or some limitation of the AMS technique.
Keywords: NUMERICAL MODELLING; LAVA TUBES; FLOW STRAIN; STRAIN PATTERN; ELLIPSOID